WHAT IS THE SIGNIFICANCE OF CONDUCTING DIDACTIC GAMES IN TEACHING ATOMIC PHYSICS COURSES IN HIGHER EDUCATION - ANVAR ABDULLA OGLI MAKHMUDOV; ABDULLA MAKHMUDOVICH KHUDAUBERGANOV (International Journal of Innovations in Engineering Research and Technology, 2021)
This article discusses the importance of the use of didactic games, which can be used in atomic physics lessons in higher education.